On the application of a work postulate to frictional contact - Jones, R.E.; Papadopoulos, P. (Archives of Mechanics, 2001)
The work postulate of Naghdi and Trapp is applied to a frictional contact interface to derive an inequality restricting the relation between slip traction and slip direction.